2017
DOI: 10.1016/j.dib.2017.05.050
|View full text |Cite
|
Sign up to set email alerts
|

Datasets on the genomic positions of the MLL1 morphemes, the ZFP57 binding site, and ZFBS-Morph overlaps in the build mm9 of the mouse genome

Abstract: While MLL1 activates gene expression in most tissues, ZFP57 represses transcription. MLL1 selectively interacts with a group of nonmethylated DNA sequences known as the MLL1 morphemes. ZFP57 associates with a methylated hexamer (ZFBS), dispersed in the genomic DNA segments known as Imprinted Control Regions (ICRs) and germline Differentially Methylated Regions (gDMRs), to maintain allele-specific gene repression. We have identified a set of composite DNA elements (ZFBS-Morph overlaps) that provides the sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 15 publications
(27 reference statements)
2
12
0
Order By: Relevance
“…In oocytes, this CGI is methylated and regulates parent-of-origin specific gene expression [28]. A previous study found a large cluster of ZFBS-Morph overlaps in the Zac1 ICR/gDMR [13]. The density-plot revealed a very robust density peak that encompasses that cluster in the intragenic CGI that corresponds to the Zac1 ICR/gDMR (Fig.…”
Section: Density Peaks Located the Icr/gdmr Of Zac1 And Candidate Icrmentioning
confidence: 79%
See 4 more Smart Citations
“…In oocytes, this CGI is methylated and regulates parent-of-origin specific gene expression [28]. A previous study found a large cluster of ZFBS-Morph overlaps in the Zac1 ICR/gDMR [13]. The density-plot revealed a very robust density peak that encompasses that cluster in the intragenic CGI that corresponds to the Zac1 ICR/gDMR (Fig.…”
Section: Density Peaks Located the Icr/gdmr Of Zac1 And Candidate Icrmentioning
confidence: 79%
“…Towards this goal, we developed a bioinformatics strategy. We built our approach on results showing that ~ 90% of the known ICRs/gDMRs included clusters of ZFBS-morph overlaps [13,16]. In order to remove background noise, we created plots to display the density of ZFBS-morph overlaps along genomic DNA.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations